Case for a Centralized Database for Waqf Administration in Malaysia - Ziyaad Mahomed; Baharom Abdul Hamid; Kinan Salim; Pahmi Ali; Wan Amir Zal; Wiaam Hassan; Fauzias Mat Nor; Fuadah Johari (Oxbridge Publishing House, 2024)
Indexed by Scopus